2014
DOI: 10.3390/systems2020186
|View full text |Cite
|
Sign up to set email alerts
|

A Sceptics View: “Kleiber’s Law” or the “3/4 Rule” is neither a Law nor a Rule but Rather an Empirical Approximation

Abstract: Early studies showed the metabolic rate (MR) of different-sized animals was not directly related to body mass. The initial explanation of this difference, the "surface law", was replaced by the suggestion that MR be expressed relative to mass n , where the scaling exponent "n" be empirically determined. Basal metabolic rate (BMR) conditions were developed and BMR became important clinically, especially concerning thyroid diseases. Allometry, the technique previously used to empirically analyse relative growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 43 publications
0
57
0
1
Order By: Relevance
“…Others claim that heterogeneous contingent factors are importantly involved in determining both the slopes and elevations of metabolic scaling relationships [10,16,23,32,[50][51][52]. As a point of departure for my discussion about the contingency versus constraints debate, I focus on published data showing that an extrinsic factor, namely ambient temperature, not only significantly affects the scaling of metabolic rate, but also does so in fundamentally different ways in ectothermic and endothermic animals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others claim that heterogeneous contingent factors are importantly involved in determining both the slopes and elevations of metabolic scaling relationships [10,16,23,32,[50][51][52]. As a point of departure for my discussion about the contingency versus constraints debate, I focus on published data showing that an extrinsic factor, namely ambient temperature, not only significantly affects the scaling of metabolic rate, but also does so in fundamentally different ways in ectothermic and endothermic animals.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, like the MTE, cell-size theory predicts that changing temperature should affect the elevation of metabolic scaling relationships, but not their slopes (but see Section 3.2.2), which again is contradicted by the results described in this study. Most other models focused on the differential scaling of various resource-demanding processes and tissues or organs with different metabolic rates (see e.g., [10,38,52]) have yet to consider how ambient temperature may affect metabolic scaling slopes (but see discussion of dynamic energy budget theory below). Furthermore, a recent study has shown that temperature acclimation does not affect the size and metabolic rate of various organs of the prawn Macrobrachium tolmerum [78].…”
Section: Implications Of Results For Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, over 150 years ago, Regnault and Reiset [166] observed that the metabolic rates of rabbits and dogs are unchanged by exposure to atmospheric oxygen levels 2-3 times above normal [167]. In the mid-1900s, several investigators also discounted the effects of oxygen supply limits on metabolic scaling because excised tissues continue to show allometric metabolic scaling in the presence of high oxygen levels (e.g., [168,169]).…”
Section: Resource-transport Modelsmentioning
confidence: 99%
“…46,47 Future research will either confirm or reject these propositions, but it is clear that many more detailed measurements of metabolic rates are required and that current theoretical attempts to explain mechanistically why metabolic rates change with increasing body size are inadequate. [48][49][50][51][52][53] Finally, we want to stress that the exact regulatory mechanisms of O 2 -dependent Figure 8. Summary of organ-and cell respiration with reference to the production/release of Adenosine-3-Phosphate (ATP) by mitochondria.…”
Section: Discussionmentioning
confidence: 99%